Body Mass Index, Blood Pressure, and Glucose Profiles in the AKRABI TENSI Exercise Program: Screening and Prevention of Non-Communicable Diseases - Deny Yuliawan; Alvi Annastasya; Era Ledi Diana; Ucup Firdaus; Windu Santoso; Wulandari Wulandari; Yudis Dwipa Yolan Anugrah; I’ana Aulia Andari (Universitas Muhammadiyah Surakarta, 2025)
Non-communicable diseases (NCDs), including hypertension, are major health problems commonly found in communities and are among the leading causes of death globally, including in Indonesia. The management of hypertension requires family support, adherence to antihypertensive medication, and the promotion of a healthy lifestyle. This community service program aimed to educate the elderly through the “AKRABI TENSI” exercise movement and to provide an overview of body mass index (BMI), blood pressure, and random blood glucose levels (RBG) as a screening and prevention effort for NCDs at the Elderly Posyandu in Padukuhan Karang Lo. This activity was carried out over seven days, from observation to evaluation, by the team as part of the Clinical Exposure (CE) 3 practice block. There were four series of activities during the implementation, including: (1) “AKRABI TENSI” exercise and deep breathing relaxation; (2) health education on hypertension prevention using the “CERDIK” approach; (3) routine health checks including blood pressure, random blood glucose (RBG), weight, and height measurements; and (4) evaluation of health education using a crossword puzzle. The educational media used included PowerPoint presentations, small banners, manual sphygmomanometers, and basic health check devices. Evaluation results showed that 78% of participants had a sufficient level of knowledge. Health screening results revealed that 33 participants (72%) had high blood pressure, while 13 participants (28%) were within the normal range. Among 46 participants, 16 had elevated blood glucose levels, while 30 had normal levels. This program highlights the need to optimize elderly Posyandu activities through continuous education and health screenings to reduce the prevalence of non-communicable diseases (NCDs) in the community.